Trust and the face - Dores, A. (2017)
Damasio´s books call for scientific cooperation between neurosciences and social sciences. He acknowledge both the epistemic limits that obstruct the free flow of knowledge between different scientific fields and Cartesian preconceptions that radically separate macro and micro analyses, societies and individuals. The face is strategically in position of mediating both worlds imaginarily untouched by one another. It challenge present scientific paradigm that presuppose the split between social and natural sciences. The face is both natural and cultural. That is the perfect research field to open to new cognitive adventures beyond the limits of science. And to help us to overcome the impasse of the development of social sciences.